UNDERPRICING PERUSAHAAN IPO DI BURSA EFEK INDONESIA TAHUN 2015-2017 DITINJAU DARI REPUTASI UNDERWRITER, UMUR PERUSAHAAN DAN UKURAN PERUSAHAAN - Asana, Gde Herry Sugiarto; Pratama, Ketut Hery Sony (Jurnal Riset Akuntansi (JUARA), 2020)
Various ways can be done by companies to fulfill their capital needs in order to develop the company to be greater. This study aims to determine the effect of underwriter reputation, company age, and company size on underpricing of IPO companies on the Indonesia Stock Exchange in 2015-2017. The population of this research were companies that conduct IPOs in the period 2015-2017 on the Indonesia Stock Exchange (IDX). The sampling method used in this study was purposive sampling with a total sample of 49 companies. The data used in this study was secondary data obtained from the company's prospectus. The analytical method used in this study was multiple linear regression analysis. The results of this study indicate that the reputation of the underwriter does not affect underpricing, the age of the company does not affect underpricing, and the size of the company influences underpricing.